The Evolutionary Dynamics of Apomixis in Ferns: A Case Study from Polystichoid Ferns. (5th November 2012) - Liu, Hong-Mei; Dyer, Robert J.; Guo, Zhi-You; Meng, Zhen; Li, Jian-Hui; Schneider, Harald
Abstract : The disparate distribution of apomixis between the major plant lineages is arguably one of the most paradoxical phenomena in plant evolution. Ferns are particularly interesting for addressing this issue because apomixis is more frequent than in any other group of plants. Here, we use a phylogenetic framework to explore some aspects of the evolution of apomixis in ferns and in particular in the polystichoid ferns. Our findings indicate that apomixis evolved several times independently in three different clades of polystichoid ferns. A lineage-wide perspective across ferns indicates a correlation between apomixis and the species richness of lineages; however BiSSE tests did not recover evidence for a correlation of apomixis and diversification rates. Instead, evidence was recovered supporting an association between the establishment of apomixis and reticulate evolution, especially in the establishment of triploid hybrids. Diversification time estimates supported the hypothesis of short living apomictic lineages and indicated a link between the establishment of apomixis and the strengthening of the monsoons caused by the lifting of the Qinghai-Tibetan plateau. In general our results supported the hypothesis for the rare establishment of apomictic lineages, high extinction risks, and low speciation rates.